(untitled) (مجلة الواحات للبحوث والدراسات, 2020)
Being aware and adhering to the scientific research ethics and to comply to all its principles is an essential input to ensure the quality and effectiveness of a scientific research, this aforementioned that was and still is the direct reason to establish a scientific revolution that the world has witnessed in all fields of life, and therefore , values of scientific research are fundamental principles for scholars and researchers to respect and comply during a scientific work. From this perspective, the researcher can acquire ethical behaviour that motivates him doing the right thing and the adequate conduct in the right place and the right time, furthermore to ensure the quality of the scientific research and the scientific researcher’s integrity. Keywords – Ethics - Quality - Scientific Research - Principles – Knowledge